Control de calidad de las arenas de la parte baja de la provincia de El Oro - Cañar Chalaco, Ronald Paúl (My University, 2023)
The main characteristic of this work is to analyze and control the quality of the sands of the different quarries in the lower part of the province of El Oro, emphasizing the sands since they are very useful for construction at the local level. The sands were brought from quarries such as. Tuco León, Zhumiral, La Iberia and Zarumilla, with which the different tests were carried out in the laboratory such as. granulometry, densities and colorimetry, with the sole purpose of establishing the different characteristics of the sands of each quarry. These sands were taken naturally from the previously mentioned rivers, and taken through a cleaning process using large sieves that exist in each quarry. It should be noted that these results obtained were compared to be able to observe and analyze which quarry obtained the best sand in the lower part of the province of El Oro, complying with specifications and requirements according to the ASTM - C33 and NTE INEN - standards. 872.
Este trabajo tiene como característica principal analizar y controlar la calidad de las arenas de las diferentes canteras de la parte baja de la provincia de El Oro, haciendo énfasis en las arenas ya que son de gran utilidad para la construcción a nivel local. Las arenas fueron traídas de canteras tales como. Tuco León, Zhumiral, La Iberia y Zarumilla, con las cuales se procedieron a realizar los diferentes ensayos en el laboratorio como. granulometría, densidades y colorimetría, con el único fin de establecer las diferentes características de las arenas de cada cantera. Estas arenas fueron sustraídas de manera natural de los ríos previamente mencionados, y llevadas por un proceso de limpieza mediante tamices grandes que existen en cada cantera. Se debe indicar que estos resultados obtenidos fueron puestos a comparación para poder observar y analizar cual cantera obtuvo la mejor arena de la parte baja de la provincia de El Oro, cumpliendo con especificaciones y requerimientos de acuerdo a la norma ASTM – C33 y NTE INEN – 872.
Keywords: CANTERA; ARENA; CALIDAD; ENSAYO